Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.4269/ajtmh.2004.71.363
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Rickettsia Africae in Patients and Ticks Along the Coastal Region of Cameroon

Abstract: Rickettsia africae was identified in seven (6%) of 118 patients with acute fevers of unknown etiology proven not to be malaria or typhoid fever from clinics along the coastal region of Cameroon by polymerase chain reaction (PCR) amplification and sequencing of the citrate synthase (gltA) and outer membrane protein A (ompA) genes of Rickettsia. The majority (71%) of the patients were female. Clinical manifestations included fever (100%), headache (71%), myalgia (71%), arthralgia (43%), pulmonary involvement (29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 21 publications
2
49
1
1
Order By: Relevance
“…The most likely reason for the dissimilarities in our findings could be attributed to the differences in protocols as different primer pairs we adopted in the studies. Other SFG rickettsial that have been detected in South Africa include Rickettsia conorii conorii, R. aeschlimannii and R. sibrica monogolitimonae [51,52] of which none was detected in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…The most likely reason for the dissimilarities in our findings could be attributed to the differences in protocols as different primer pairs we adopted in the studies. Other SFG rickettsial that have been detected in South Africa include Rickettsia conorii conorii, R. aeschlimannii and R. sibrica monogolitimonae [51,52] of which none was detected in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…Despite high seroprevalence to R. africae among native Africans, nearly all acute cases of ATBF described in the literature have occurred in European or American travelers (145,205,273). Recently however, Ndip et al reported cases of ATBF documented by serology (26 patients) and molecular techniques (7 patients) among indigenous patients in Cameroon (212,213).…”
Section: Emerging Pathogens (1984 To 2004)mentioning
confidence: 99%
“…Efforts to determine the epidemiology and ecology later re-emerged in 2004 when anti-rickettsial IgM antibodies were detected in some Cameroonian patients along the coastal region of Cameroon (Ndip et al, 2004a). These results were further confirmed by detection of R. africae DNA in about 6% of acutely ill febrile patients (Ndip et al, 2004b). Human infections or the agent has been detected in all regions of southern Cameroon where epidemiologic investigations have been made (Figure 3).…”
Section: Epidemiologymentioning
confidence: 96%
“…The agent was later isolated in A. hebraeum ticks in Zimbabwe in 1990, and in 1992, the first isolate from a patient was obtained Kelly et al, 1994). The pathogen has been detected in many other African countries including Senegal , Ethiopia (Stephany et al, 2009) and Cameroon (Ndip et al, 2004a;Ndip et al, 2004b). In the following, we give a synopsis of our current knowledge of African tick bite fever in Cameroon.…”
Section: The Genus Rickettsiamentioning
confidence: 99%
See 1 more Smart Citation